Nematode communities as bioindicators of forest soil health: responses to degradation and restoration practices - Olaide Ayodele Oladeji; Jonathan Jeremiah Atungwu; Solabomi Olaitan Ayoade; Joshua Tunde Olaifa; Maryam Adeniran Adeleke; Moses Akintayo Aborisade (Integrated Environmental Assessment and Management, 2026)
Abstract Deforestation and forest degradation fundamentally alter subterranean ecosystems and the biological health of soils, yet belowground recovery trajectories remain poorly integrated into restoration monitoring frameworks. Soil nematodes are powerful bioindicators, but their application in forests has largely extrapolated from agricultural paradigms without accounting for forest-specific food web structures and dynamics. This review consolidates current understanding of nematode community responses to factors contributing to forest degradation, including deforestation, soil compaction, organic matter depletion, and alterations in nutrient dynamics. It also examines the impact of various restoration initiatives on recovery trajectories. We assess the theoretical principles and practical applications of nematode-based ecological indicators, including the maturity index, enrichment index, structure index, and channel index, as diagnostic tools for evaluating forest soil health. The review examines the relationship between changes in nematode trophic group composition and fluctuations in decomposition pathways, microbial dynamics, and plant-soil feedback mechanisms. Through case studies from tropical, temperate, and boreal forests, we identify knowledge gaps regarding nematode responses to innovative restoration techniques. We provide a conceptual framework for integrating nematode community analysis into forest soil health monitoring and offer practical recommendations for utilizing nematode indicators to inform adaptive management strategies for recovery of degraded and protection of healthy forest soils.